Froebel's Gifts: How the Kindergarten Movement Changed the American Familiy - Philipp Ager; Francesco Cinnirella (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Public educators and philanthropists in the late 19th century United States promoted the establishment of kindergartens in cities as a remedy for the social problems associated with industrialization and immigration. Between 1880 and 1910, more than seven thousand kindergartens opened their doors in the United States, serving both a social and educational function. We use newly collected city-level data on the roll-out of the first kindergartens to evaluate their impact on household outcomes. We find that in cities with a larger kindergarten exposure, families significantly reduced fertility, with the strongest decline appearing in families that were economically disadvantaged and with an immigrant background. Households reduced fertility because kindergarten attendance increased returns to education, but it also led to higher opportunity costs for raising children. Indeed, we show that children exposed to kindergartens were less likely to work during childhood and, instead, stayed longer in school, had more prestigious jobs, and earned higher wages as adults. Finally, we find that exposure to kindergartens particularly helped immigrant children from non-English-speaking countries to gain English proficiency. Their attendance also generated positive language spillover effects on their mothers, illustrating the importance of early childhood education for the integration of immigrant families.
Keywords: N31; J13; I25; O15; 330; kindergarten education; family size; fertility transition; returns to preschool education; quantity-quality trade-off